Kant as a Baylean atheist - Laursen , John Christian (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article argues that if Pierre Bayle had read Immanuel Kant, he might have thought Kant was an atheist. It begins from Bayle's definitions of atheism, which came out especially in his study of Spinoza. Spinoza was an atheist, Bayle thought, in part because he used strange definitions of God which no one else used. If one reads Kant on religion, one discovers many such strange locutions. And Bayle thought that the meaning of "God" included such elements as personality, liberty, providence, and beneficence, and that if these are denied one does not believe in the "God" of most people. Since Kant denied each of these in one way or another, Bayle would have thought of him as an atheist.